The Effect of Story Face Strategy Towards Students' Reading Comprehension of Recount Text - Marleni, Lusi; Diana, Anita (ELT-Lectura, 2024)
This study aims to determine whether using the story face strategy affects students’ reading comprehension in tenth-grade recount texts for the academic year 2022/2023. The research was conducted on tenth-grade MIA students at SMAN 2 Bangkinang Kota. The study involved 56 students who were divided into 2 classes, namely class X MIA 3 as the control class and X MIA 5 as the experimental class. Each class consists of 28 students. The experimental class uses the story face strategy as a learning strategy and the control class is taught using an English textbook. The data were analyzed using the SPSS 25 program. Based on the results obtained, the average value of students in the experimental class was 70.89 and 48.93 in the control class. The data obtained showed a significance (2-tailed) 0.001 < 0.05. This means that H0 is rejected and Ha is accepted. This shows that there are differences in students’ reading comprehension between students who are taught using the story face strategy and students who are taught using English textbooks. Based on the findings, it can be concluded that the story face strategy is effective for students’ reading comprehension of recount text.